"It feels like wearing a giant sandbag." Adolescent and parent perceptions of fatigue in paediatric multiple sclerosis. (November 2016) - Carroll, Susan; Chalder, Trudie; Hemingway, Cheryl; Heyman, Isobel; Moss-Morris, Rona
Abstract: Aim: Fatigue is one of the most common and disabling symptoms of paediatric MS, associated with depressed mood, impaired school performance and lower quality of life. Fatigue in children and adolescents with MS (caMS) is poorly understood, and effective treatments for fatigue are currently lacking. No qualitative studies have previously examined fatigue in caMS. Thus, the objectives were (a) to explore experiences of fatigue in paediatric MS and (b) to gain insight into how caMS and their parents respond to and manage fatigue. Methods: In-depth semi-structured qualitative interviews were conducted with 15 caMS and 13 of their parents, either face-to-face or via telephone. Inductive thematic analysis was primarily used, incorporating elements of grounded theory. Results: Five key themes were identified in the data. Participants described mentally and physically exhausting fatigue, which they perceived as uncertain and uncontrollable. Parents expressed concern about caMS' well-being and future because of fatigue, whilst caMS discussed the implications of disclosure or non-disclosure of fatigue to peers and teachers. An additional overarching theme addressed participants' emotional responses to fatigue. Participants stressed the need for better guidance on fatigue management. Interpretation: This study provides a unique insight into the experience and management of fatigue in paediatric MS from the perspective of both caMS and parents. Some findings echoed experiences of fatigue in other populations, whilst new factors in paediatric MS also emerged. Fatigue management interventions involving caMS, parents and teachers should be developed and implemented in clinical practice. Highlights: Fatigue is a highly disruptive symptom for caMS and parents. Parents and caMS experience fatigue as an uncertain, uncontrollable symptom. Fatigue evokes concern in parents for caMS' well-being and future. CaMS highlight the implications of disclosure or non-disclosure of fatigue. Implementing fatigue management strategies in clinical practice is imperative.